Enhancing Arabic Language Learning in Higher Education: Leveraging E-Campus as an Online Learning and Evaluation Platform - Ritonga, Mahyudin; Mudinillah, Adam; Ardinal, Eva; Tauhid, Tauhid; Nurdianto, Talqis (Jurnal Ilmiah Peuradeun, 2024)
The Industrial Revolution era is a time that requires the connection between technology and various aspects of life, including education. But there are still many educational institutions that have not responded well regarding the use of technology in learning, therefore this study aimed to determine the use of E-campus as an online learning media and Arabic learning evaluation media in higher education. The research was conducted at Islamic State University of Batusangkar, the approach used was quantitative with a survey research design. The results of the study stated that E-campus could be used as an alternative in carrying out Arabic language learning, completeness of features, ease of access, and clarity of access as evidence that E-campus was effectively used for online classes in Arabic language learning, until now no features have been found in E-Campus that can be used to evaluate and measure Arabic speaking skills. The utilization of E-campus in Arabic language learning brings great benefits and influences for lecturers and students. The limitation of this study is that researchers did not design an E-campus platform that has complete features to measure four Arabic speaking skills for students, therefore future researchers can conduct research aimed at creating an E-campus model that has more complete features.